The Influence of Skin Permeability and Electric Fields on Drug Permeation in Transdermal Systems: A Simulation-Based Study Using Pascal - Muhammad Taufik; Syahrial A (Kappa Journal, 2024)
Transdermal drug delivery systems (TDDS) offer a promising non-invasive approach for drug administration, yet their effectiveness is often constrained by the permeability of the skin and the properties of the drug. This study investigates the combined impact of skin permeability and electric fields on drug permeation through the skin, using simulation data generated by a custom-developed program in Pascal. The simulation, based on Fick’s Law of Diffusion, incorporates the effects of iontophoresis (electric fields) on drug transport, adjusting parameters such as skin permeability, electric field strength, and drug characteristics. The results demonstrate that both skin permeability and electric field intensity significantly influence the rate of drug permeation. Notably, the highest flux was observed when both electric field strength (1.0 mA/cm²) and enhanced skin permeability (3.5 coefficient) were applied, with drug flux increasing by up to 5 times compared to passive diffusion. These findings underscore the substantial benefits of combining skin permeability enhancers, such as microneedles or chemical enhancers, with electric field application, offering valuable insights for developing more efficient TDDS. The results suggest that optimizing both parameters can significantly improve drug delivery, especially for low-permeability drugs.